2022
DOI: 10.1002/slct.202201068
|View full text |Cite
|
Sign up to set email alerts
|

Mn‐Dependent Morphology and Structure of SnS2 Nanosheets and the Photocatalytic Performance

Abstract: Transition metal dichalcogenides have potential application in photocatalysis. Here, we synthesized Mn‐(un) doped tin disulfide materials for photocatalytic degradation by hydrothermal method. The XRD, SEM, TEM, EDS, XPS, BET, UV‐Vis and PL were employed to analyze their structures, morphologies, surface chemical state and photoelectronic properties. The results show that as‐prepared tin disulfide displays hexagonal morphology of nanotablets, and Mn‐doped tin disulfide consists of quasi‐hexagonal thin nanotabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…48 In the experiment, a certain amount of the capture agent was added to the solution, and the process was referred to those of the previous work. 49 It was observed that the degradation activity decreased significantly after L-ascorbic acid and AgNO 3 were added to the RhB solution (Fig. 6a), and the degradation rate was reduced by 51.6% and 80.6%, respectively (Fig.…”
Section: Photocatalytic Mechanismmentioning
confidence: 94%
“…48 In the experiment, a certain amount of the capture agent was added to the solution, and the process was referred to those of the previous work. 49 It was observed that the degradation activity decreased significantly after L-ascorbic acid and AgNO 3 were added to the RhB solution (Fig. 6a), and the degradation rate was reduced by 51.6% and 80.6%, respectively (Fig.…”
Section: Photocatalytic Mechanismmentioning
confidence: 94%
“…Several strategies have been widely adopted to enhance photocatalytic performance, including morphological modification, 68,69 structural engineering, 70,71 and heterostructure formation. [72][73][74] Each of these strategies has unique advantages.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental problems have become more and more serious because of the discharge of industrial wastewater including organic dyes. [1,2] The general methods of removing organic dyes from wastewater include physical adsorption, biodegradation, and chemical precipitation. Besides, photocatalysis technology can meet the requirements of green, safety, economy, and high efficiency.…”
Section: Introductionmentioning
confidence: 99%